Ambiguous roles and potential therapeutic strategies of innate lymphoid cells in different types of tumor - Wang, Shijie (Oncol Lett, 2020)
Recent years have witnessed a significant development in the current understanding of innate lymphoid cells (ILCs) and their roles in the innate immune system, where they regulate tissue homeostasis, inflammation, as well as tumor surveillance and tumorigenesis. Based on the limited studies of ILCs in cancer, ILCs may be classified into three subgroups depending on their phenotypic and functional characteristics: Group 1 ILCs, which include natural killer cells and ILC1s; Group 2 ILCs, which only contain ILC2s and Group 3 ILCs, which comprise of LTi cells and ILC3s. Group 1 ILCs predominantly exert antitumor activities, while Group 2 ILCs and Group 3 ILCs are predominantly procarcinogenic in nature. In different types of tumor, each ILC subset behaves differently. Current research is focused on investigating how ILCs may be manipulated and employed as therapeutic strategies for the treatment of cancer. The present review aimed to summarize the characteristics and effects of ILCs in the context of tumor immunology, and provide novel insight into the pro- or anti-tumor activities of ILCs in different types of malignancy, including solid tumors, such as those in the gastrointestinal tract, lung, breast, bladder or prostate, as well as melanoma, further to hematological malignancies, with the aim to highlight potential therapeutic targets for the treatment of cancer.